KEADILAN, TATA KELOLA, DAN KEBERLANJUTAN: KERANGKA SPAB DALAM REFORMASI AGRARIA MODERN - Muhamad Rafi Akbar Maulana; Rezza Fauzi Muhammad Fahmi; Muhammad Fiqri Fauzan; Muhammad Rouf Habiballoh (Universitas Negeri Surabaya, 2026)
In this article, we discuss the role of Land-Based Agrarian Reform Schemes (LRAs) in promoting agrarian justice, governance, and sustainability in Indonesia. We focus on tenure conflicts, land tenure inequality, and the lack of protection for vulnerable groups. The objectives are as follows: (1) to explain the role of LRAs in the current agrarian reform agenda; (2) to explain the essential components that underpin substantive and procedural justice in agrarian management; and (3) to identify factors that determine the success and failure of LRAs implementation at the local level. Qualitative-descriptive methods are used through literature studies, policy reviews, and comparative analyses of relevant local practices. Data are collected through thematic analysis of regulatory documents, program reports, academic publications, and secondary field findings. The analysis focuses on the interactions between actors, institutional capacities, participation mechanisms, and the socio-political context that shapes LRAs implementation. The results show that LRAs can represent rights and distribute resources if supported by appropriate tenure maps, significant participation, transparency, and sustained support. However, this success is not evenly distributed. This